Lesions of the prepuce and penis in rams: A retrospective study - Falchi, L.; Pau, S.; Ledda, M.; Melosu, V.; Zedda, MT (Veterinary research communications, 2023)
In the ovine reproductive management, a thorough breeding soundness evaluation including specific inspection of the male genital tract represents a valuable tool for assessing the reproductive potential of a selected subject and for diagnosing genital disorders. During examination, accurate inspection on penis and prepuce is necessary, since conditions affecting these structures may hamper regular coitus. Records from 1270 males undergoing breeding soundness evaluation (n = 1232) or admitted for genital disorders to the Section of Obstetrics and Gynaecology (n = 38) of the Department of Veterinary Medicine, were collected, and lesions of penis and prepuce were therefore classified. The data collected revealed that 47/1270 rams examined presented lesions of the penis and prepuce. The most frequent condition was urolithiasis accounting for over 2% of the cases, followed by lack of the urethral process (0.39% incidence), lack of the glans penis and hypospadias (0.23% cases). Moreover, most of the conditions (40%) were observed in animals less than 2 years old, suggesting the importance of a careful breeding soundness evaluation in animals at young age.